2015
DOI: 10.1016/j.molcel.2015.02.031
|View full text |Cite
|
Sign up to set email alerts
|

ATR-Mediated Phosphorylation of FANCI Regulates Dormant Origin Firing in Response to Replication Stress

Abstract: SUMMARY Excess dormant origins bound by the minichromosome maintenance (MCM) replicative helicase complex play a critical role in preventing replication stress, chromosome instability and tumorigenesis. In response to DNA damage, replicating cells must coordinate DNA repair and dormant origin firing to ensure complete and timely replication of the genome; how cells regulate this process remains elusive. Herein, we identify a member of the Fanconi Anemia (FA) DNA repair pathway, FANCI, as a key effector of dorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 80 publications
9
153
2
Order By: Relevance
“…ATR activity is necessary both for the stabilization of stalled replication forks and for fork restart following replication stress. On one hand, ATR inhibition results in the increased firing of origins in the absence of DNA damage (Shechter et al, 2004), but on the other hand, under replication stress, ATR-dependent phosphorylation of 'Fanconi anemia, complementation group I' (FANC1) inhibits the firing of dormant origins (Chen et al, 2015b). In addition, ATR deficiency in aphidicholine-treated cells causes incomplete replication of regions with fragile sites (Casper et al, 2002;Paulsen and Cimprich, 2007).…”
Section: Atr In Replication Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…ATR activity is necessary both for the stabilization of stalled replication forks and for fork restart following replication stress. On one hand, ATR inhibition results in the increased firing of origins in the absence of DNA damage (Shechter et al, 2004), but on the other hand, under replication stress, ATR-dependent phosphorylation of 'Fanconi anemia, complementation group I' (FANC1) inhibits the firing of dormant origins (Chen et al, 2015b). In addition, ATR deficiency in aphidicholine-treated cells causes incomplete replication of regions with fragile sites (Casper et al, 2002;Paulsen and Cimprich, 2007).…”
Section: Atr In Replication Stressmentioning
confidence: 99%
“…When a replication fork encounters a gene that is being transcribed, the Mec1/ATR pathway phosphorylates nucleoporin components to release the transcribed chromatin, which is attached to the nuclear envelope (Bermejo et al, 2011), thereby preventing torsional-stressinduced fork reversal. Hence, the ATR response ensures robust replication through different means -by stabilizing replication forks (Paulsen and Cimprich, 2007), preventing fragile-site expression (Casper et al, 2002;Cha and Kleckner, 2002), influencing replication origin firing (Chen et al, 2015b;Shechter et al, 2004) and also coordinating replication with transcription (Bermejo et al, 2011), as well as by triggering the replication stress response (Flynn and Zou, 2011) (see poster). Under conditions of replication stress, a balance between the amounts of RPA and ssDNA appears to be crucial for the stability of the replication fork (Toledo et al, 2013).…”
Section: Atr In Replication Stressmentioning
confidence: 99%
“…In addition, the relationship between the FA proteins and ATR may be mutual and of equally importance. The recruitment of ATRIP was reported to be essential for FANCD2 monoubiquitination and FANCI phosphorylation, and the latter is catalyzed by ATR kinase [70]. The FA core complex E3 was found to also enhance the binding of ATRIP to the damaged chromatin site [71].…”
Section: Fa Signaling and Master Regulators Of Cellular Stress Rementioning
confidence: 99%
“…In yeast, Fan1 is capable of conferring ICL repair activity in the absence of the UBZ domain (Fontebasso et al 2013). One potential role of the interaction between FAN1 and FANCD2/FANCI outside of ICL repair includes the processing of replication forks under normal or replicative stress conditions (Schlacher et al 2012;Chaudhury et al 2014;Chen et al 2015). Most recently, it has been shown that the UBZ domain of FAN1 is essential for the processing of replication forks and protection against chromosome instability after treatment with HU and MMC (Lachaud et al 2016).…”
Section: Fan1 and Icl Repairmentioning
confidence: 99%